Telaah Kritis Kehadisan Teks “Menuntut Ilmu Di Waktu Kecil Laksana Mengukir Di Atas Batu” - Rajab Z; H Rajab; Hj Rustina N (Jurnal Ulunnuha, 2020)
This study aims to determine whether the text "Demanding Knowledge in Childhood is Like Carving on a Rock", whether it is a hadith of the Prophet. or not and to explain the meaning content of the text which is popular in that society. This determination is important because this text is still being debated about its traditions, it is still found in teaching materials in schools and lecture materials of preachers and preachers on the one hand and the threat of the Prophet. against the perpetrators of lies on behalf of the Prophet. on the other. This research is a qualitative descriptive study that relies on literature sources. The research was carried out by first exploring the hadith books to find the existence of the texts in these books and then testing its hadith by using the theory of authenticity of hadiths built by Ibn al-Salah, that a hadith must meet validity rules, namely continuity. sanad, narrators are 'ādil and dābit and avoid illah and shudhudh. From this test, the conclusion is that the text under study was relying on the Prophet. cannot be accounted for, some of the narrations are not based on the Prophet, but on al-Hasan al-Basri, while the narrations that are based directly on the Prophet. the quality is very low, because the sanad is cut off and the transmitters do not have the characteristic 'adālah. However, this historical text does not mean it contains goodness and needs to be removed from the treasury of Muslims. This text is still a good thing, it can be followed and practiced, as long as it does not rely on the Prophet.